Nurse Appointment Information System Using the Simple Additive Weighting Method: Study At One of The Foundations in Bandung - Nengsih Nengsih; Asep Ririh Riswaya; Marjito Marjito; Solihin Solihin (P3M, STIE Pasundan, Bandung, Indonesia., 2025)
Swift technological advancements have impacted multiple areas, including healthcare. The One of The Foundations in Bandung, which provides home care services for the elderly and ailing, encounters difficulties with its nurse booking system, which remains manually operated via WhatsApp and phone calls. This method yields inefficiencies, substantial administrative overhead, and potential human errors. This study aims to develop a web-based information system utilizing the Simple Additive Weighting (SAW) method to enhance the efficiency of nurse booking and selection. The SAW technique was selected for its capacity to manage multi-criteria decision-making, including factors such as healthcare tool utilisation, experience, age, and evaluations. The system includes online booking, criterion administration, evaluation weighting, and integrated reporting. This system enhances nurse booking and selection efficiency, alleviates administrative loads, and reduces potential errors, thereby significantly impacting healthcare service efficacy and advancing information technology in the healthcare sector.